Theoretical Study of Light Emission in Europium-Chelate-Doped Polymer Optical Fibres. (December 2018) - García-Ramiro, B; Arrue, J; Illarramendi, M A; Jiménez, F; Zubia, J
Abstract: We analytically and computationally study the generation of light in poly (methyl methacrylate) polymer optical fibres (PMMA POFs) doped with a typical coordination complex, or chelate, of Eu 3+ . The system has been modelled by means of four rate equations that describe the temporal and spatial evolution of the generated power, the pump power, and the concentrations of excited ligands and europium ions. For this paper, the system has been solved in stationary state by using the fourth-order Runge-Kutta method. The results show the influence of several parameters of light sources based on europium-chelate-doped POFs both on the optimum fibre length and on the output power, including the effect of the attenuation of the emitted red light. Additionally, we have derived a simplified analytical expression that serves to model the evolution of the generated power as it propagates while the pump power is still non-negligible.